HUBUNGAN PERSONAL HYGIENE DENGAN KEJADIAN DEMAM TIFOID DI WILAYAH KERJA PUSKESMAS TUMARATAS - Seran, Eunike Risani; Palandeng, Henry; Kallo, Vandri (JURNAL KEPERAWATAN, 2015)
Abstract: The typhoid fever is a kind of disease that caused by Salmonella typhi and related with poor practice of personal hygiene. The highest occurrence of typhoid fever in 2014 was in the Tumaratas public health center subdistrict west of Langowan with 157 case. The purpose of this study was to determine the relationship among personal hygiene with the occurrence of typhoid fever in the working area of Tumaratas public health center subdistrit west of Langowan. Quantutative method with case-control. The population case of this study are all of Typhoid Fever patients on January-September 2014, based on medical record. Population control not patients of typhoid fever (hypertensive patients) on January-September 2014, based on medical record. The sampels of this study are 21 cases and 21 controls. The research instruments are questionnaires. The data of research processed with Chi Square test at a level of 95% (Î±=0,05). The resulth show are relationship with the habits of washing hands before eating (p=0,029), the habits of washing raw food to be eaten immediately (p=0,029) and the habits of eating outside the house (p=0,031) with the occurrence of typhoid fever. Meanwhile, there is no correlation between hand washing after defecation (p=0,160). Conclusion: good personal hygiene can afeect the incidence of typhoid fever. Suggestion through of this research are inccrease awareness of good personal hygiene needs to be impoved. Key Word : Personal Hygiene, Typhoid Fever Abstrak: Demam tifoid adalah penyakit yang disebabkan oleh infeksi Salmonella Typhi dan berhubungan erat dengan personal higiene yang buruk. Angka kejadian demam tifoid di wilayah kerja Puskesmas Tumaratas Kecamatan Langowan Barat tahun 2014 adalah 157 orang. Tujuan untuk mengetahui hubungan antara personal higiene dengan kejadian demam tifoid di Wilayah Kerja Puskesmas Tumaratas Kecamatan Langowan Barat. Metode kuantitatif dengan pendekatan kasus kontrol. Populasi kasus semua penderita demam tifoid bulan Januari-September 2014 berdasarkan rekam medik. Populasi kontrol bukan dari penderita demam tifoid (pasien hipertensi) bulan Januari-September 2014 berdasarkan rekam medik. Sampel penelitian 21 responden kasus dan 21 responden kontrol. Instrumen penelitian menggunakan kuesioner. Data hasil penelitian diolah menggunakan uji Chi Square dengan tingkat kemaknaan 95% (Î±=0,05). Hasil menunjukan ada hubungan antara kebiasaan mencuci tangan sebelum makan (p=0,029), kebiasaan mencuci bahan mentah langsung konsumsi (p=0,029) dan kebiasaan makan di luar rumah (p=0,031) dengan kejadian demam tifoid. Sedangkan kebiasaan mencuci tangan setelah BAB tidak ada hubungan dengan kejadian demam tifoid (p=0,160). Kesimpulan: personal higiene yang baik dapat dapat mempengaruhi angka kejadian demam tifoid. Saran melalui penelitian ini peningkatan kesadaran akan personal higiene yang baik perlu ditingkatkan. Kata kunci : Personal Higiene, Demam Tifoid